Explosion evolution behavior of methane/air premixed gas in a closed pipe filled with a bio-based porous material. (15th June 2022) - He, Yunlong; Fang, Quan; Yuan, Bihe; Cao, Chengran; Zhan, Yuanyuan; Chen, Xianfeng; Huang, Chuyuan; Zhang, Yuduo; Ding, Qingquan
Highlights: Luffa sponge was applied in the gas safety protection field for the first time. An efficient bio-based flame retardant was synthesized. Most of the raw materials are natural renewable resources. Flame-retardant luffa sponge has an excellent flame and explosion-proof effect. The flame and explosion-proof mechanisms of luffa sponge were explored. Abstract: Porous materials are widely employed in the gas explosion-proof field because of their abilities to dissipate shock wave energy. Luffa sponge is a biomass material with three-dimensional network structure. Thus, it will be a promising porous explosion-proof candidate material. However, luffa sponge is flammable, limiting its development in the flame and explosion-proof field. In this work, a bio-based flame retardant integrating acid catalyst, char-forming agent and foaming source was synthesized. Then the flame-retardant luffa sponge is prepared through impregnation method, and it is employed to the gas explosion-proof field for the first time. The flame-retardant luffa sponge can completely prevent the explosive flame spread, and its explosion overpressure decay ratio can reach up to 84%. The flame-retardant luffa sponge has superior flame and explosion-proof performances, and it can be produced on a large scale. This work provides a novel idea for the research and development of efficient flame and explosion-proof materials by the utilization of renewable resources.